Dynamic Load Energy Dissipation Of 3 Storey Reinforced Concrete Building with Inverted V-Braced Dampers - Chew, Wai Meng (2021)
Earthquake is a natural disaster that leads to uncountable life sacrificed and people are losing their family and houses in the blink of eye. The earthquake event that happens in East Malaysia had brought the attention of the people especially seismic and structural engineer. However, most of the existing reinforced concrete buildings in Malaysia does not include the structure earthquake resistance design. Therefore, this research is focusing on the seismic energy dissipation of low-rise reinforced concrete building with and without inverted V-braced dampers under various dynamic loadings and important for the development of construction industry in future. A 1 bay 1 frame 3 storey reinforced concrete model is constructed with a scale factor 1:8. The scaled model with and without inverted V-braced dampers are analysed through the shaking table test under eleven different sets of peak ground acceleration. The results and discussion show the spectral acceleration at each floor increases as the PGA increases and roof floor has the highest spectral acceleration. Besides, maximum inter-storey drift happens at first storey indicates first storey is more vulnerable to earthquake. The seismic energy dissipation by the model with inverted V-braced damper at later stage is the highest with an increment of 5.34 kNmm and 5.60 kNmm as compared to bare frame. The output of the structural damage reliability analysis of reinforced concrete shows no damage to model under PGA of 0.1 g and 0.16 g; minor damage to model under PGA of 0.2 g, 0.3 g and 0.4 g; extensive damage to model under PGA of 0.5 g, 0.6 g, 0.7 g, 0.8 g and 0.9 g; model collapse under PGA 1.0 g. In conclusion, the novelty of this research is the inverted V-braced damper improved the seismic dissipation energy through reducing the base shear and lateral displacement from the building.